HEALTH ECONOMICS: EPISTEMOLOGICAL ANALYSIS - Machado dos Santos, Adelcio; Antonio Córdova Ransolin, Marco; Tenconi, Daniel; Marton, Roberto; Sprandel da Silva, Solange (Health and Society, 2026)
This article aims to conduct a theoretical discussion on Health Economics, addressing its foundations, importance, and applications within the context of public health policies. Using a qualitative and bibliographic approach, the study explores classical and contemporary contributions to the field, highlighting concepts such as scarcity, efficiency, equity, and resource allocation. The analysis shows that health, as a public good and a social right, requires specific economic tools to face its challenges, particularly in public systems like the Brazilian one. Economic evaluation in health is presented as a key tool for efficient resource management, allowing the selection of interventions with the best cost-benefit ratio. However, the article also addresses the limitations and challenges of the field, including the ethical complexity of economic decisions, the lack of qualified data, and the structural inequalities of health systems. Finally, future perspectives in Health Economics are discussed, involving the strengthening of value-based analyses, the incorporation of technologies, and the training of qualified professionals. It is concluded that Health Economics significantly contributes to the sustainability of health systems by promoting more rational, fair, and evidence-based decisions.